Perlindungan Hukum Merek Terkenal Dari Tindakan Persaingan Usaha Tidak Sehat di Era Digital - Mahali Soelianegara, Raden Naila Nadira Mahali Soelianegara; Najwa Aulia Nabila (CV. Denasya Smart Publisher, 2025)
This research investigates the legal protection afforded to well-known trademarks against unfair competition in the digital era. The proliferation of e-commerce and online platforms has created new challenges for trademark protection, with instances of infringement, counterfeiting, and other forms of unfair competition becoming increasingly prevalent. This study aims to analyze the adequacy of existing Indonesian legal frameworks, including the Trademark Law and the Law on Prohibition of Monopoly and Unfair Business Competition, in addressing these challenges. Employing a qualitative research method involving legal doctrinal analysis and case studies of relevant court decisions, the study examines the effectiveness of current legal mechanisms in protecting well-known trademarks online. The findings reveal gaps in the legal framework and suggest areas for improvement, such as enhanced enforcement mechanisms and regulations specifically tailored to the digital environment. The conclusion emphasizes the need for a more robust and adaptable legal framework to effectively safeguard well-known trademarks in the dynamic landscape of digital commerce